Development of small and medium enterprises (SMEs) in FELDA scheme: challenges and policy prospect - Mohd Sauh, Shuhaimi; Abdullah, Moha Asri; Abdul Rahman, Rozailin (Zes Rokman Resources, 2019)
Small and Medium Enterprises (SMEs) are the pillars of the Malaysian economy. They contribute to the economy in many ways such as creating job opportunities, alleviating poverty, providing decent goods and services, serving complimentary inputs to large firms, diversifying products/inputs, training entrepreneurs and workers, and helping a supply chain of business networks. The government of Malaysia has introduced various SMEs policies since independence to ensure SMEs success and able to go through various economic turbulences and be sustainable. However, limited studies have been conducted to examine the impact of those policies on SMEs development in the rural area, particularly the FELDA scheme. The aim of this paper is to examine the SMEs development in the FELDA scheme. Specifically, this study evaluates the SMEs contribution to ASEAN, Malaysia and the FELDA scheme; identifying challenges faced by SMEs in Malaysia and FELDA scheme, and considers proposed policies for SMEs development in the FELDA scheme. This study utilizes past literature from earlier scholars and published reports related to SMEs in ASEAN, Malaysia and the FELDA scheme. The methodology of study largely is descriptive and qualitative in nature. This study also reveals two key findings. First, SMEs in Malaysia accounted for more than one-third of Malaysia’s GDP. The study discloses SMEs in the FELDA scheme who also plays a pivotal role in rural economic development. FELDA has provided a good entrepreneurial ecosystem for SMEs development in the FELDA scheme. Secondly, SMEs in Malaysia have faced five major challenges, namely, access to finance, human resources, technology adoption, market potential information and global competition. In the case of SMEs in the FELDA scheme, the entrepreneurs have faced two main challenges namely access to finance and market accessibility beyond the FELDA scheme. Finally, this study helps to understand the challenges faced by SMEs in the FELDA scheme. This study further provides several policy recommendations that can be considered to improve the SMEs performance in FELDA scheme